PENGARUH LIKUIDITAS, SOLVABILITAS, RENTABILITAS PADA KOPERASI SERBA USAHA WAHIDIYAH “AL-AMIN” KECAMATAN MOJOROTO KOTA KEDIRI (EFFECT OF LIQUIDITY SOLVENCY, PROFITABILITY ON WAHIDIYAH BUSINESS OPERATIONS “AL-AMIN” SUBSCRIPTION MOJOROTO KEDIRI). - Suhud Wasiono (CAHAYA AKTIVA, 2018)
The purpose of this research is to know the influence of Liquidity, Solvability and Profitability on Multipurpose Business Cooperative Wahidiyah "Al-Amin" Subscription Mojoroto Kediri. Multi Business Cooperative Wahidiyah as a business entity Wahidiyah. Multi Business Cooperative Wahidiyah as a business entity Wahidiyah who participate in realizing the prosperity of Wahidiyah pengamal in particular and society in general. For that Multifunctional Business Cooperative Wahidiyah need to build himself to be strong. The method used is Library Research and Field Research and Financial Ratio The method used is Library Research and Field Research and Financial Ratio Analysis of liquidity, solvency, profitability of 2015 to 2017. Research and Discussion Results are as Research and Discussion Results are as follows: The number of members 300 people in 2015 and 362 people in 2016 or up 20.6% and in 2017 to 409 people or 12.9%. The amount of principal and mandatory savings in 2015 Rp.116.148.200, - and in 2016 Rp.147.033.200, - or rose 26.6% and in 2017 to Rp.178.796.200 or up 21.6%. Assessment of Liquidity by 2015 = 2.05 (2: 1) and 2016 = 2.03 (2: 1) in 2017 to 2.03 (2: 1). Normal Standard 2: 1 means Wahidiyah Multipurpose Cooperative " Al-Amin "is able to pay off short-term debt when it matures. Assessment of Solvency in 2015 = 0.73 (7:10) and 2016 = 0.21 (2:10) in 2017 to 0.56 (6:10) Normal Standard = 8: 1 means Multipurpose Business Cooperative "Al -Amin "able to pay short-term debt as well as long-term Assessment of Rentability in 2015 amounted to 16.76%, by 2016 by 10.89% in 2017 by 12.63%. Normal Standards are 10% to 20%, meaning Wahidiyah Business Unions "Al-Amin" in obtaining profit is still normal because it is still in the range of 10% to 20%. The influence of liquidity, solvency and profitability as a whole can be seen that Wahidiyah Multipurpose Business Cooperative "Al-Amin" Subscription Mojoroto Kediri able to pay both short-term and long-term debt and gain normal profit from 2015 until 2017. Keywords : Liquity, solvency, profitability